2014
DOI: 10.1016/j.devcel.2014.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Differential Regulation of Microtubule Severing by APC Underlies Distinct Patterns of Projection Neuron and Interneuron Migration

Abstract: Coordinated migration of distinct classes of neurons to appropriate positions leads to the formation of functional neuronal circuitry in the cerebral cortex. Two major classes of cortical neurons, interneurons and projection neurons, utilize distinctly different modes (radial vs. tangential) and routes of migration to arrive at their final positions in the cerebral cortex. Here, we show that adenomatous polyposis coli (APC) modulates microtubule (MT) severing in interneurons to facilitate tangential mode of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 56 publications
0
20
0
Order By: Relevance
“…At least some APC proteins also regulate actin dynamics, working together with Diaphanous (Breitsprecher et al, 2012; Jaiswal et al, 2013), to control focal adhesion turnover (Juanes et al, 2017). When considering cytoskeletal effects of APC loss, however, it is critical to rule out places where Wnt signaling itself regulates downstream cytoskeletal events (e.g., Elbaz et al, 2016;Eom et al, 2014;Hayden et al, 2007;Nakagawa et al, 2017;Yokota et al, 2009). Other destruction complex or signalosome proteins also have cytoskeletal roles.…”
Section: Apc Mutations In Colorectal Cancer Target Specific Aspects Omentioning
confidence: 99%
“…At least some APC proteins also regulate actin dynamics, working together with Diaphanous (Breitsprecher et al, 2012; Jaiswal et al, 2013), to control focal adhesion turnover (Juanes et al, 2017). When considering cytoskeletal effects of APC loss, however, it is critical to rule out places where Wnt signaling itself regulates downstream cytoskeletal events (e.g., Elbaz et al, 2016;Eom et al, 2014;Hayden et al, 2007;Nakagawa et al, 2017;Yokota et al, 2009). Other destruction complex or signalosome proteins also have cytoskeletal roles.…”
Section: Apc Mutations In Colorectal Cancer Target Specific Aspects Omentioning
confidence: 99%
“…On the other hand, prior work has shown that katanin regulates neuron development in vivo. For instance, defective MT severing is associated with neuronal abnormalities, including Alzheimer's disease where abnormal aggregation of the MT-associated tau protein might interfere with its role in preventing excess MT severing (Qiang et al, 2006;Eom et al, 2014;Mao et al, 2014). Additionally, katanin is essential for both male and female fertility via modulating the assembly of meiotic spindles (McNally et al, 2006;Loughlin et al, 2011;O'Donnell et al, 2012;Smith et al, 2012).…”
Section: Ktn80 Defines the Precision Of Mt Severing Via Specific Targmentioning
confidence: 99%
“…Like other plus-end stabilizing proteins, APC was found to be greatly enriched in the nervous system during axon growth and navigation (Bhat et al, 1994 ; Koester et al, 2007 ). A series of works emerged that pointed to GSK3-modulated APC in multiple roles within the early nervous system, including neuronal polarity, migration, and axon specification, providing some added assurance that this interaction was an important regulator of MT dynamics in neural development (Dobashi et al, 2000 ; Shi et al, 2004 ; Koester et al, 2007 ; Purro et al, 2008 ; Eom et al, 2014 ; Mohn et al, 2014 ; Onouchi et al, 2014 ). APC preferential localization was shown to accumulate on the “turning” side of the growth cone as it encountered a substrate border, predicting turning behavior (Koester et al, 2007 ; Figure 2 ).…”
Section: The +Tip Of the Iceberg: Cytoplasmic Linker Associated Protementioning
confidence: 99%